HOW MANY CHIRONOMID HEAD CAPSULES ARE ENOUGH? A STATISTICAL APPROACH TO DETERMINE SAMPLE SIZE FOR PALAEOCLIMATIC RECONSTRUCTIONS - Larocque I. (My University, 2001)
Chironomid-inferred temperature reconstruction has been shown to be accurate but the method is tenuous and time consuming. With the increased importance of high-resolution studies, more samples should be analysed, increasing the time taken to obtain climate reconstructions. Here, the number of head capsules that should be used to be both time effective and statistically representative for climate reconstruction was tested. In 30 of the 33 samples, counting 50 head capsules was enough to obtain a temperature reconstruction similar to the one obtained by counting 150 or more head capsules. Counting 90 head capsules or more gave the lowest differences between temperature estimates with 200 head capsules. There was a significant increase in the number of new taxa found in relation with the number of head capsules counted. For ecological purposes, the more head capsules that are identified, the better is the representation of the population.
Keywords: CHIRONOMID-INFERRED TEMPERATURE; SAMPLE SIZE; REPRESENTATIVITY